Second species of Augochlorodes (Hymenoptera: Halictidae: Augochlorini) with known males and first record for the genus in Argentina - González Vaquero, Rocío Ana (2014)
The bee genus Augochlorodes Moure, up to now only known from Brazil, is recorded for the first time for Argentina. Augochlorodes politus Gonçalves & Melo was found in the south of the province of Buenos Aires, mideastern Argentina, being the southernmost record for the genus. The female of A. politus is redescribed and the male described for the first time, being the second male known for this genus. The phylogenetic position of Augochlorodes among Augochlorini is briefly discussed.